SMS Gateway based E-mail to SMS and SMS to E-mail Delivery Service Application - Suherman, Suherman; Afriantoro, Irfan; Saputra, Dian (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The very rapid development of information and communication technology has a direct influence on human life, namely the internet and cell phones, the internet makes it easy to access very valuable and very cheap information that does not depend on location anywhere, connecting very long distances to communicate, technological developments always has a very high role and contributes to the direction of development in the world of multimedia, education, entertainment and others, this application uses Microsoft Visual Basic.NET software. and to design the application using E-mail and GSM cellphones.Keywords: MDLC, Learning Media, Mathematics, Scratch.